Effects of ferric carboxymaltose on hospitalisations and mortality rates in iron‐deficient heart failure patients: an individual patient data meta‐analysis. (24th April 2017) - Anker, Stefan D.; Kirwan, Bridget‐Anne; van Veldhuisen, Dirk J.; Filippatos, Gerasimos; Comin‐Colet, Josep; Ruschitzka, Frank; Lüscher, Thomas F.; Arutyunov, Gregory P.; Motro, Michael; Mori, Claudio; Roubert, Bernard; Pocock, Stuart J.; et al.
Abstract: Aims: Iron deficiency (ID) is a common co‐morbidity in patients with heart failure (HF) and has been suggested to be associated with poor prognosis. Recently completed double‐blind randomised controlled trials (RCTs) studying HF patients with ID have shown improvements in functional capacity, symptoms and quality of life when treated with i.v. ferric carboxymaltose (FCM). This individual patient data meta‐analysis investigates the effect of FCM vs. placebo on recurrent hospitalisations and mortality in HF patients with ID. Methods and results: Individual patient data were extracted from four RCTs comparing FCM with placebo in patients with systolic HF and ID. The main outcome measures were recurrent cardiovascular (CV) hospitalisations and CV mortality. Other outcomes included cause‐specific hospitalisations and death. The main analyses of recurrent events were backed up by time‐to‐first‐event analyses. In total, 839 patients, of whom 504 were randomised to FCM, were included. Compared with those taking placebo, patients on FCM had lower rates of recurrent CV hospitalisations and CV mortality [rate ratio 0.59, 95% confidence interval (CI) 0.40–0.88; P = 0.009]. Treatment with FCM also reduced recurrent HF hospitalisations and CV mortality (rate ratio 0.53, 95% CI 0.33–0.86; P = 0.011) and recurrent CV hospitalisations and all‐cause mortality (rate ratio 0.60, 95% CI 0.41–0.88; P = 0.009). Time‐to‐first‐event analyses showed similar findings, with somewhat attenuated treatment effects. The administration of i.v. FCM was not associated with an increased risk for adverse events. Conclusions: Treatment with i.v. FCM was associated with a reduction in recurrent CV hospitalisations in systolic HF patients with ID.